Lewis acid-catalyzed redox-neutral amination of 2-(3-pyrroline-1-yl)benzaldehydes via intramolecular [1,5]-hydride shift/isomerization reaction - Jiang, Chun-Huan; Lei, Xiantao; Zhen, Le; Du, Hong-Jin; Wen, Xiaoan; Xu, Qing-Long; Sun, Hongbin (Beilstein Journal of Organic Chemistry, 2014)
Lewis acid-catalyzed redox-neutral amination of 2-(3-pyrroline-1-yl)benzaldehydes via intramolcular [1,5]-hydride shift/isomerization reaction has been realized, using the inherent reducing power of 3-pyrrolines. A series of N-arylpyrrole containing amines are obtained in high yields.
Keywords: catalysis; C–H activation; hydride-shift; Lewis acid; redox reaction